Evaluasi Radiologis Pneumotoraks Spontan Sekunder pada Pasien dengan Tuberkulosis Paru Kasus Relaps - Pertiwi Permata Putri; Tantri Dwi Kaniya (Medula, 2019)
Pneumothorax is one of emergency case which needs to be immidiately treated. Spontaneus secondary pneumothorax (SSP) is one type of pneumothorax with history of pulmonary disease. Pulmonary tuberculosis (TB) is the most common etiology of SSP. Estimated incidence rate of SSP caused by pulmonary TB is 0,6-1,4%. Diagnosis can be made by history-taking and physical examination, but other examination like radiology imaging is important to evaluate and follow-up the patient so that an appropriate and optimum management can be given. A 31 years old male complained breathlessness since 3 days before hospitalized with history of pulmonary TB 8 years ago and had completed all of the drug regiment. in this last 1 month, patient experienced dry cough, sub-febrile fever, malaise, and frequently sweating at night without activity. Radiological finding on the day of admission: pleural white line and avascular hiperluscent, conclusion: pneumothorax dextra. Chest radiograph after water-sealed drainage showed improvement, early-detection of complication, and ensure the position of the drain.